Penguatan Tata Kelola Pemilu Digital melalui Evaluasi Implementasi SIREKAP di KPU Provinsi Sulawesi Utara - Tangka, George; Longkutoy, Desmond; Mokodaser, Wilsen Grivin (Universitas Klabat, 2025)
The 2024 simultaneous elections relied on the Vote Recapitulation Information System (SIREKAP) to enhance transparency, but its implementation in North Sulawesi faced technical and non-technical challenges. This community service activity evaluated SIREKAP's implementation using the CIPP model (Context, Input, Process, Product) through in-depth interviews and FGDs with 30 election organizers. Key findings revealed three critical issues: (1) uneven internet infrastructure causing 40% of remote polling stations to fail in data uploads, (2) low digital literacy among 65% of polling officers (KPPS), and (3) only 85% accuracy of the OCR feature in reading C1 forms. Recommendations include simulation-based training, offline mode development, and open-source code audits. The study underscores the need for a holistic approach to digital election transformation, integrating technical, human resource, and infrastructure aspects